A methodology to assess immigrants land use patterns in concentrated/sprawled environments (the case of Porto Metropolitan Area) - Emília Malcata Rebelo (2011)
The main objective of this article is to develop a methodology of cartographic analysis to support municipal decisions concerning attraction, location, and distribution of immigrants in metropolitan areas, ensuring respective integration. This innovative methodology is aimed at identifying settlement patterns (and their respective intensities) adopted by specific groups of immigrants according to territorial characteristics (i.e., concentration, sprawl, and dispersion) and the immigrants' own ethnic features, in relation to correspondent patterns of the whole population. It is applied as a case study to the Porto Metropolitan Area (Portugal). This paper discusses sociological reasons for the concentrated or dispersed behaviors shown by different ethnic groups and how the behaviors shape the morphological and typological characteristics of the immigrant settlements. The application of this methodology to different urban realities makes it possible to (I) monitor the evolution of indicators concerning immigrants and metropolitan territorial characteristics; (2) analyze and compare settlement behaviors exhibited by different ethnic groups in relation to the correspondent behaviors of the native population; (3) critically inspect the evolution of the integration of different ethnic groups; and (4) define and apply urban policies aimed at attracting, distributing, and locating immigrants in the metropolitan areas, simultaneously ensuring socioeconomic territorial sustainability.